ESTETIKALÍQ TÁRBIYANÍŃ PEDAGOGIKA HÁM FILOSOFIYADAǴÍ ÁHMIYETI - Abdiev, Berdax Turǵanbaevich (SCIENCE and SOCIETY, 2026)
This article provides an in-depth analysis of aesthetic education, one of the current pressing problems, and especially discusses the importance of aesthetic education. An attempt has been made to broadly reveal the scientific and philosophical contradictions related to the development of aesthetic education among students.